2017
DOI: 10.1002/syn.21961
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effect of sodium cyclamate and propylparaben on pentylenetetrazol‐induced seizures in zebrafish

Abstract: Screening for novel anticonvulsant drugs requires appropriate animal seizure models. Zebrafish provide small, accessible, and cost-efficient preclinical models applicable to high-throughput small molecule screening. Based on previous results in rodents, we have here examined the effects of artificial sweetener sodium cyclamate and antimicrobial agent sodium propylparaben on a model of pentylenetetrazole (PTZ)-induced seizures in zebrafish. Sodium cyclamate reduced the bursts of hyperactivity, the spasms, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Zebrafish can be utilized to investigate the pathogenesis of epilepsy, screening of anti-epileptic drugs, validation of target and most importantly can be modeled into novel seizure model recapitulating the clinical phenotype. Compared to rodents seizure model, zebrafish seizure model possesses a benefits of minimal drugs requirement, shorter duration of assays, resemblance and easy quantification of seizure-like behavior, possibility of recording abnormal neuronal discharge by electroencephalography (EEG) and its transparent nature ( Buenafe et al, 2013 ; Pisera-Fuster et al, 2017 ; Zhang et al, 2020 ). Despite the availability of Kainic acid ( Mussulini et al, 2018 ), PTZ ( Mussulini et al, 2013 ) and Pilocarpine ( Paudel et al, 2020e ) induced seizure model in adult zebrafish, no earlier study has reported a longitudinal (10 days) chronic seizure model in adult zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish can be utilized to investigate the pathogenesis of epilepsy, screening of anti-epileptic drugs, validation of target and most importantly can be modeled into novel seizure model recapitulating the clinical phenotype. Compared to rodents seizure model, zebrafish seizure model possesses a benefits of minimal drugs requirement, shorter duration of assays, resemblance and easy quantification of seizure-like behavior, possibility of recording abnormal neuronal discharge by electroencephalography (EEG) and its transparent nature ( Buenafe et al, 2013 ; Pisera-Fuster et al, 2017 ; Zhang et al, 2020 ). Despite the availability of Kainic acid ( Mussulini et al, 2018 ), PTZ ( Mussulini et al, 2013 ) and Pilocarpine ( Paudel et al, 2020e ) induced seizure model in adult zebrafish, no earlier study has reported a longitudinal (10 days) chronic seizure model in adult zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, zebrafish larvae develop a spontaneous swimming pattern at 5 days post-fertilization (dpf), making it an appropriate model organism to study neurobehavior under seizures . Regarding epilepsy research, the zebrafish model offers the advantages of resemblance to seizure-like phenotypes and the possibility of electroencephalography (EEG) assays, making it preferable in preclinical epilepsy research, especially for early stage screening of anti-epileptic agents. …”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that embryonic exposure to PrP triggered anxiety-like neurobehavioral response in zebrafish, which is correlated with oxidative-stress-induced apoptosis in the head of the larvae [ 27 ]. Nevertheless, PrP was suggested to reduce the excitability of hippocampal neurons in rats [ 62 ], and to have anticonvulsant effects on pentylenetetrazol-induced seizures in zebrafish [ 63 ], demonstrating the potential for use in anticonvulsant drugs. In this study, cell cavitation, cytomorphosis and blurred cell boundaries were found in the brain of mosquitofish, the deleterious effects of PrP on the physiological function of brain should be noteworthy to illuminate the safety and toxicity mechanisms.…”
Section: Discussionmentioning
confidence: 99%